2023
DOI: 10.3390/ijms241914693
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of IL-1β-Mediated Necroptosis in Neurodevelopment Impairment after Neonatal Sepsis in Rats

Zhimin Liao,
Qing Zhu,
Han Huang

Abstract: The mechanism of long-term cognitive impairment after neonatal sepsis remains poorly understood, although long-lasting neuroinflammation has been considered the primary contributor. Necroptosis is actively involved in the inflammatory process, and in this study, we aimed to determine whether neonatal sepsis-induced long-term cognitive impairment was associated with activation of necroptosis. Rat pups on postnatal day 3 (P3) received intraperitoneal injections of lipopolysaccharide (LPS, 1 mg/kg) to induce neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“… 67 Additionally, an in-vivo study suggested that IL-1β is involved in neurodevelopment. 68 In conclusion, the onset and progression of PHN may be closely associated with IL-1β, as evidenced by this meta-analysis.…”
Section: Discussionsupporting
confidence: 54%
“… 67 Additionally, an in-vivo study suggested that IL-1β is involved in neurodevelopment. 68 In conclusion, the onset and progression of PHN may be closely associated with IL-1β, as evidenced by this meta-analysis.…”
Section: Discussionsupporting
confidence: 54%
“…Numerous cell death processes, including necrosis/necroptosis, pyroptosis, and ferroptosis, are connected to the release of DAMPs ( Murao et al, 2021 ). All these different types of cell death have been reported in the pathological development of sepsis and cognitive dysfunction associated with sepsis ( Fu et al, 2019 ; Zhou et al, 2019 ; Chu et al, 2022 ; Liao et al, 2022 ; Wang J. et al, 2022 ; Liao et al, 2023 ). Our recent research showed that necrostatin-1 and xenon were protective against sepsis-induced brain injury by preventing necroptosis.…”
Section: Feed-forward Loop In Neuroinflammationmentioning
confidence: 99%
“…Our recent research showed that necrostatin-1 and xenon were protective against sepsis-induced brain injury by preventing necroptosis. Necroptosis was activated via receptor interacting protein 1/3 (RIP1/3), which contributed to impaired neurodevelopment in neonatal sepsis survivors (Liao et al, 2022(Liao et al, , 2023. The NLRP3/caspase-1 pathway-induced pyroptosis has also been linked to cognitive impairment following sepsis.…”
Section: Feed-forward Loop In Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation